The role of medical expenses in the saving decision of elderly: a life cycle model - Xinwen Ni (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2019)
In this paper, we develop an multi period overlapping generation framework to investigate agents' consumption and saving decisions, inequality and welfare among elderly. We assume that agents are heterogeneous in the non-asset income and the medical expenditure. In order to explicitly analyze the e ects of medical expenditure, we conduct three counterfactual exercises. We successively shut down the heterogeneity in labor income, in the level and in the dispersion of medical expenses respectively. By comparing the benchmark with the counterfactual results, we nd that in general wealth inequality decreases with age, and income uncertainty contributes the most to wealth inequality. Both average consumption and consumption inequality increase with age. Consumption inequality largely tracks income inequality. Though uncertainty in medical expenditures has little e ect on consumption inequality, a higher level of medical expenditures may exacerbate consumption inequality. Meanwhile, the average saving of elderly exhibits an inverse-U shape with age. The impacts on average saving are similar both in benchmark and in counterfactual exercises. Welfare increases with age.
Keywords: C00; 330; Income Inequality; Social Mobility; Price-to-rent ratio